ANALISIS TANTANGAN DAN ETIKA DALAM PENDIDIKAN DIGITAL - Junaidi; Lukman Al Faht; Mohamad Akbar; Andi Warisno; Nila Wati Tajuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of information and communication technology has driven the transformation of education towards a digital learning system. Digital education provides various conveniences, such as broad access to information, learning time flexibility, and increased interaction through online platforms. However, the implementation of digital education also faces various challenges, including technology access gaps, low digital literacy, data security, and decreased social interaction. In addition, the application of digital ethics is needed to ensure the responsible use of technology by educators and learners. This article aims to examine various challenges and ethics in digital education as well as provide recommendations for creating an effective, safe, and character-building learning environment. The method used is a literature study by analyzing various literatures related to digital education. The results of the study show that the success of digital education is not only determined by technological sophistication but also by the readiness of human resources and the proper implementation of digital ethics.